BlueTable: Connecting Wireless Mobile Devices on Interactive Surfaces Using Vision-Based Handshaking - Wilson, Andy; Sarin, Raman (GI '07 Proceedings of Graphics Interface 2007, 2007)
Associating and connecting mobile devices for the wireless transfer of data is often a cumbersome process. We present a technique of associating a mobile device to an interactive surface using a combination of computer vision and Bluetooth technologies. Users establish the connection of a mobile device to the system by simply placing the device on a table surface. When the computer vision process detects a phone-like object on the surface, the system follows a handshaking procedure using Bluetooth and vision techniques to establish that the phone on the surface and the wirelessly connected phone are the same device. The connection is broken simply by removing the device. Furthermore, the vision-based handshaking procedure determines the precise position of the device on the interactive surface, thus permitting a variety of interactive scenarios which rely on the presentation of graphics co-located with the device. As an example, we present a prototype interactive system which allows the exchange of automatically downloaded photos by selecting and dragging photos from one cameraphone device to another.